Bone marrow-derived mesenchymal cell differentiation toward myogenic lineages: Facts and perspectives - Galli, D.; Vitale, M.; Vaccarezza, Mauro (Hindawi Publishing Corporation, 2014)
Bone marrow-derived mesenchymal stem cells (BM-MSCs) are valuable platforms for new therapies based on regenerative medicine. BM-MSCs era is coming of age since the potential of these cells is increasingly demonstrated. In fact, these cells give origin to osteoblasts, chondroblasts, and adipocyte precursors in vitro, and they can also differentiate versus other mesodermal cell types like skeletal muscle precursors and cardiomyocytes. In our short review, we focus on the more recent manipulations of BM-MSCs toward skeletal and heart muscle differentiation, a growing field of obvious relevance considering the toll of muscle disease (i.e., muscular dystrophies), the heavier toll of heart disease in developed countries, and the still not completely understood mechanisms of muscle differentiation and repair.